2012
DOI: 10.1515/reveh-2012-0012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particulate matter air pollution on C-reactive protein: a review of epidemiologic studies

Abstract: Inflammatory response is implicated as a biologic mechanism that links particulate matter (PM) air pollution with health effects. C-reactive protein (CRP), an important acute-phase reactant with profound proinflammatory properties, is used clinically as an indicator of the presence and intensity of inflammation. In vitro and in vivo animal studies suggest that CRP levels increase in response to PM exposure, but there was no consistency in epidemiologic studies. Herein, a systematic review was conducted to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
83
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 84 publications
(96 reference statements)
2
83
5
Order By: Relevance
“…There seem to be mixed results with regard to associations between ambient or individual-level PM 2.5 exposure and CRP; some studies have shown positive associations (Huttunen et al, 2012;Zhao et al, 2013), whereas other studies have reported no effect on CRP levels in the circulation (Liu et al, 2009;Ruckerl et al, 2007a;Strak et al, 2013;Wu et al, 2012). A review concluded that there was an association between air pollution exposure and elevated levels of CRP in children, whereas there were inconsistent results on healthy adults (Li et al, 2012). Other studies have reported positive associations between exposure to ambient PNC and CRP in healthy individuals (Hertel et al, 2010) and in coronary heart disease patients (Delfino et al, 2008(Delfino et al, , 2009Panasevich et al, 2009;Ruckerl et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There seem to be mixed results with regard to associations between ambient or individual-level PM 2.5 exposure and CRP; some studies have shown positive associations (Huttunen et al, 2012;Zhao et al, 2013), whereas other studies have reported no effect on CRP levels in the circulation (Liu et al, 2009;Ruckerl et al, 2007a;Strak et al, 2013;Wu et al, 2012). A review concluded that there was an association between air pollution exposure and elevated levels of CRP in children, whereas there were inconsistent results on healthy adults (Li et al, 2012). Other studies have reported positive associations between exposure to ambient PNC and CRP in healthy individuals (Hertel et al, 2010) and in coronary heart disease patients (Delfino et al, 2008(Delfino et al, , 2009Panasevich et al, 2009;Ruckerl et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms involved in the health effects of PM include pulmonary and systemic inflammation, oxidative stress, altered cardiac autonomic function, altered balance between coagulation and fibrinolysis, endothelial and microvascular dysfunction, atherosclerosis progression and plaque instability, as studied in panel and crosssectional studies with short-term exposure assessed from monitoring stations or after controlled exposure (Brook et al, 2010). However, results have shown less consistency for prognostic markers for cardiovascular risk, including blood markers reflecting inflammation such as C-reactive protein (CRP) and circulating leukocyte counts, cell expression of adhesion molecules and impaired endothelial function (Li et al, 2012;Pope et al, 2011;Ruckerl et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In healthy volunteers and in patients with CVD, exposure to air pollution is associated with an increase in the circulatory levels of inflammatory biomarkers, including TNF-a, IL6, IL8 and CRP [2,[7][8][9][10][11][12][13][14]. To our knowledge, the available evidence on such an association in COPD patients is very scarce [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore hard to draw a single conclusion regarding the epidemiological evidence, however, the general impression was that positive associations with ambient air pollution are indicated for blood markers of inflammation, whereas results for coagulation markers remain inconsistent (Ruckerl et al, 2011). Li et al (2012) published a review of epidemiological studies on the effect of PM air pollution on C-reactive protein (CRP). They concluded that findings among the healthy general population are inconsistent, but there is suggestive evidence that higher PM levels during the observation period tended to induce stronger inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%